Taste-Masked Flucloxacillin Powder Part 1: Optimisation of Fabrication Process Using a Mixture Design Approach - Okhee Yoo; Sam Salman; Britta S. von Ungern-Sternberg; Lee Yong Lim (MDPI AG, 2023)
It is extremely challenging to formulate age-appropriate flucloxacillin medicines for young children, because flucloxacillin sodium (FS) has a lingering, highly bitter taste, dissolves quickly in saliva, and requires multiple daily dosing at relatively large doses for treating skin infections. In this paper, we describe a promising taste-masked flucloxacillin ternary microparticle (FTM) formulation comprising FS, Eudragit EPO (EE), and palmitic acid (PA). To preserve the stability of the thermolabile and readily hydrolysed flucloxacillin, the fabrication process employed a non-aqueous solvent evaporation method at ambient temperature. Optimisation of the fabrication method using a mixture design approach resulted in a robust technique that generated stable and reproducible FTM products. The optimised method utilised only a single solvent evaporation step and minimal amounts of ICH class III solvents. It involved mixing two solution phases-FS dissolved in ethanol:acetone (1:4 v/v), and a combination of EE and PA dissolved in 100% ethanol-to give a ternary FS:EE:PA system in ethanol: acetone (3:1 v/v). Solvent evaporation yielded the FTMs containing an equimolar ratio of FS:EE:PA (1:0.8:0.6 w/w). The fabrication process, after optimisation, demonstrated robustness, reproducibility, and potential scalability.